Differentiating Hypertrophic Cardiomyopathy from Athlete’s Heart: A Diagnostic Challenge in Sports Cardiology - A Narrative Review - Braksal, Barbara; Cieślewicz, Karolina; Częczek, Kacper; Minik, Bartosz; Szymańska-Zdyb, Kinga; Nowaczek, Patrycja; Mirkowski, Krzysztof; Szurek, Zuzanna Wanda; Chyła, Zofia Julia; Miroński, Adam (Quality in Sport, 2026)
Background. Long-term athletic training induces structural, functional, and electrical cardiac adaptations known as athlete’s heart. In some athletes, these physiological changes overlap with hypertrophic cardiomyopathy, creating a diagnostic grey zone. Aim. The objective of this narrative review was to discuss current approaches to differentiating hypertrophic cardiomyopathy from athlete’s heart in sports cardiology. Materials and methods. Publications available in PubMed and Scopus from 2017–2026 were reviewed. The final set comprised 30 freely accessible full-text sources, including narrative reviews, systematic reviews, imaging studies, consensus statements, and clinical guidelines. Results. Differentiation requires integration of clinical history, family history, ECG, echocardiography, cardiac magnetic resonance, rhythm monitoring, genetic testing, exercise assessment, and longitudinal observation. Athlete’s heart is usually supported by proportional chamber enlargement, preserved function, high exercise capacity, and absence of myocardial fibrosis. Hypertrophic cardiomyopathy is suggested by disproportionate or focal hypertrophy, small left ventricular cavity, abnormal ECG findings, arrhythmias, fibrosis, symptoms, or positive family history. Conclusions. A multimodal and individualized diagnostic strategy is essential to reduce sudden cardiac death risk while avoiding unnecessary restriction of healthy athletes from sport.